A comparative multimodal analysis of restaurant reviews from two geographical contexts. (February 2017) - Chik, Alice; Vásquez, Camilla
In this article, the authors offer a comparative approach to the analysis of a popular internet genre – user-generated restaurant reviews – sampled from two different websites ( OpenRice and Yelp ), which have emerged from two different geographic contexts (Hong Kong and the US). Their investigation reveals both similarities and differences of in terms of review format, content discussed and the use of several semiotic resources, such as the posting of photographs, the use of emoticons and emoji, and the expressive use of orthography and punctuation. The authors demonstrate that, while many of the formal properties of the genre are quite similar, some variations in review content may reflect underlying cultural differences. Furthermore, they show not only how the website's architecture can either constrain or encourage the use (or non-use) of particular semiotic resources, but also suggest that other variables (i.e. orthographic systems, review community norms) may interact with medium factors.